371 SLEEP APNEA AND HYPERALDOSTERONISM IN PATIENTS WITH RESISTANT HYPERTENSION. (1st January 2005) - Pratt-Ubunama, M. N.; Nishizaka, M. K.; Harding, S. M.; Calhoun, D. A.
Abstract : Introduction: Recent studies have observed that there is a high degree of correlation between obstructive sleep apnea (OSA) and hypertension (HTN), particularly among patients with resistant HTN. The mechanism by which sleep apnea contributes to the development of resistant HTN, however, remains unclear. We hypothesize that OSA may cause resistant HTN through stimulation of aldosterone secretion. Methods: Consecutive subjects referred to the University of Alabama at Birmingham (UAB) hypertension clinic for resistant HTN were prospectively evaluated with an early morning plasma rennin activity (PRA) and plasma aldosterone concentration (PAC). A 24-hour urine collection for aldosterone, sodium and creatinine was also obtained during an ad-lib diet. All subjects were on a stable antihypertensive regimen without use of potassium-sparing diuretics. Subjects were also evaluated by full-night polysomnography at the UAB Sleep-Wake Disorders Center. The number of apnea-hypopnea events/hr or respiratory disturbance index (RDI) was determined in all subjects. Also measured was the % of total sleep time spent with oxygen saturations # 90%, known as the hypoxic index (HI). Results: Biochemical assessment and polysomnography were performed on a total of 32 patients with resistant HTN. The RDI was positively and significantly correlated with PAC (r = .51, p = .004), aldosterone/PRA ratio (ARR) (r = .52, p = .003) and BMI (r = .42, p = .02) in all subjects. The HI positively and significantly correlated with PAC (r = .40, p = .03), ARR (r = .43, p = .02) and BMI (r = .38, p = .04) in all subjects. (figure ) Conclusion: These data are the first to demonstrate a direct association between aldosterone levels and OSA in patients with resistant HTN. These results suggest that OSA may contribute to the development of resistant HTN by stimulating aldosterone secretion.